2015
DOI: 10.1177/0143034315584696
|View full text |Cite
|
Sign up to set email alerts
|

Indian adolescents’ cyber aggression involvement and cultural values: The moderation of peer attachment

Abstract: Although research on cyberbullying and cyber aggression is growing, little attention has been given to examinations of these behaviors among adolescents in Asian countries, particularly in India. The present study examined the relationships among cyber aggression involvement and cultural values (i.e. individualism, collectivism), along with peer attachment as a moderator in these associations, while controlling for gender and faceto-face aggression involvement. Participants were 480 adolescents (ages 13-to 15-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
13
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 54 publications
4
13
0
2
Order By: Relevance
“…These differences are explained by the authors by cultural characteristics and different online activities and infrastructure, but also the legal, societal and political characteristics of each country. This meets other research by Wright, Kamble and Soudi (2015), for instance, comparing the prevalence of cyberbullying between countries with cultures based on collectivism (China), individualism (Japan) or with mixed background (India), which shows that cultural differences have an impact. The authors adopt a risk-factor approach and identify that the youngest and most isolated people, as well as off-line victims, tend to be more at risk of being exposed to self-harm sites, to online hate and to suffer bigger negative consequences.…”
supporting
confidence: 88%
“…These differences are explained by the authors by cultural characteristics and different online activities and infrastructure, but also the legal, societal and political characteristics of each country. This meets other research by Wright, Kamble and Soudi (2015), for instance, comparing the prevalence of cyberbullying between countries with cultures based on collectivism (China), individualism (Japan) or with mixed background (India), which shows that cultural differences have an impact. The authors adopt a risk-factor approach and identify that the youngest and most isolated people, as well as off-line victims, tend to be more at risk of being exposed to self-harm sites, to online hate and to suffer bigger negative consequences.…”
supporting
confidence: 88%
“…For this reason, relationships with peers critically affect the expression of aggression in both males and females (Zara and Farrington, 2009; Casey and Beadnell, 2010). Many studies have confirmed that the quality of an adolescent’s relationships with peers is the first risk or protective factor for the expression of antisocial or aggressive behavior (Brown and Bakken, 2011; Burton et al, 2013; Wright et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Laible et al (2000) also demonstrated that attachment to peers affected aggression; additionally, the authors showed that this influence appeared to be greater than that of attachment to parents. Similarly, Wright et al (2015) reported that adolescents with higher scores on the assessment of attachment to peers were less involved in aggressive behaviors. Conversely, lower scores on the attachment to peers assessment were a significant risk factor for the emergence of threatening or aggressive behaviors.…”
Section: Attachment To Parents and Peers And Aggressionmentioning
confidence: 94%
See 1 more Smart Citation
“…According to their findings, all sub-scales from the Human Values Scale (responsibility, friendship, respect, honesty, tolerance, and pacifism) predicted cyberbullying. Wright, Kamble, and Soudi (2015) examined the relationships between cyber aggression and cultural values, as well as the effect of peers on this relationship, over 480 adolescents in India. That study's findings revealed that cyberbullying and cyber-victimization positively correlate to individualistic values and negatively correlate with collectivist values, and peer commitment negatively correlates to cyber aggression.…”
Section: Discussionmentioning
confidence: 99%